Assessing Transboundary‐Local Aerosols Interaction Over Complex Terrain Using a Doppler LiDAR Network. Issue 12 (22nd June 2021) - Huang, Tao; Li, Yue; Cheng, Jack C. H.; Haywood, Jim; Hon, K. K.; Lam, David H. Y.; Lee, Olivia S. M.; Lolli, Simone; O'Connor, Ewan James; Lee, Harry F.; Wang, Mengya; Yim, Steve H. L.
Abstract: Transboundary‐local aerosols interaction requires to be comprehensively understood in urban air quality research. A year‐long intensive observation of the atmospheric boundary layer (ABL) at multiple sites in Hong Kong was conducted using a four‐Doppler Light Detection and Ranging (LiDAR) network with different scanning modes. Results show that heterogeneity of the ABL in terms of mixing layer height and wind shear was induced by orographic topography. Interaction between local and advected aerosol layers during a transboundary air pollution (TAP) episode was identified by the network. During TAP episode, downward transport of transboundary aerosol relied on small scale eddies with weak wind speed in nighttime, while the transport of surface local aerosol to upper level was the dominated process in daytime, but the heterogeneity of the ABL affected by terrain determined the capacity of the mixing, eventually resulting in the opposite transport direction of aerosols in the transboundary‐local aerosols interaction. Plain Language Summary: Upper level aerosol transported from remote places brings difficulties to urban air quality forecast. To identify the advected aerosol in the atmospheric boundary layer (ABL) and assess the further impacts after its occurrence, a four‐Doppler LiDAR network in Hong Kong was implemented. Upper level advected aerosol layer was captured by the network, and our results show that complex terrain can lead to the spatial differences in the mixing layer height and wind shear, which stand for the characteristics of the ABL. After the advected aerosol arrived at the upper level over Hong Kong, small eddies in the weak wind condition can help to move the aerosol downward to the ground at night. After sunrise, surface accumulated aerosol was driven upward by the turbulent mixing, which was mainly caused by buoyancy. However, the differences in the ABL characteristics affect this upward transport, and finally resulted in two different transport patterns. Key Points: Terrain induced heterogeneity of the atmospheric boundary layer in terms of mixing layer height and wind shear was found Spatiotemporal variations in transboundary aerosol at upper level were identified by the four‐LiDAR network Terrestrial and marine atmosphere boundary layers determined the process of transboundary‐local aerosols interaction via turbulence